A Gender Perspective on Health Policies and Programs: An Overview of Frameworks and Experiences - Lingam, L.; Bhushan, A.; Kumar, R. (Springer Nature Singapore, 2024)
The need for “gender-responsive” policy-making that recognizes that individuals are “constrained in different and often unequal ways” based on their gender has been recognized for decades. However, the literature is relatively thin with regard to what comprises gender-responsive policies and programs and how to conduct a gender analysis of these. This initial chapter to Part IV of the handbook titled “A Gender Perspective on Health Policymaking and Programming in South Asia,” begins with an overview of the theoretical landscape for health policy analysis and moves on to key frameworks, principles and approaches developed for analyzing the gender-responsiveness of health policies and programs. It then maps the gender and health policy context in the South Asian region using selected indicators reported at global and national levels before delving into two policy areas to highlight certain commonalities and divergences in policy orientation in the region. The first analyzes the plans for health reform stated in the national health policies of selected South Asian countries and the second the gender-biased legal and policy context of abortion. The chapter suggests that current approaches to analyzing the gender-responsiveness of health policies and programs place insufficient emphasis on the gendered norms and values that underpin policies and the broader political and economic context in which policy-making happens. It argues that overlooking these aspects can impede progress on transforming gender relations and achieving gender equality. The chapter concludes by contextualizing policy research using a gender lens as presented in the papers from South Asia contained in this part of the handbook.
Keywords: Gender-responsive health policies and programs; Health policy; Health program; Gender analysis; National health plans; South Asia; Abortion policies